Overview of Guidance and Counseling Program Design at Senior High School (SMA) Level: Compliance with Standardized Program Structure - Oktadinata, Dwi; Herdi, Herdi (IAIN Kudus, 2025)
Overview of Guidance and Counseling Program Design at Senior High School (SMA) Level: Compliance with Standardized Program Structure. The design of the Guidance and counseling program is one of the determinants of the success of Guidance And Counseling services in schools. The guidance and counseling program is developed through a systematic process based on needs assessment and is designed to meet the program structure. This article aims to provide an overview of the development of the GUIDANCE AND COUNSELING program based on its suitability to the program structure consisting of (1) Rationale, (2) Legal Basis, (3) Vision and Mission, (4) Description of Needs, (5) Objectives, (6) Program Components, (7) Service Areas, (8) Operational Plan, (9) Theme/Topic Development, (10) Evaluation, Reporting and Follow-up, (11) Facilities and Infrastructure, (12) Budget. This study uses a descriptive qualitative approach by studying documents (document studies) namely the guidance and counseling program developed in 3 (three) schools in Jakarta, Banten and Bandung. The analysis results show that Private High School A in Jakarta is in the Fair category by fulfilling 60% of the aspects that need to be displayed in the program design, State High School B Banten and State High School C Bandung are in the Good category by obtaining final scores of 66% and 63%, respectively. This study also found several things that need to be considered by Counselors in developing guidance and counseling programs, namely the accuracy of selecting assessments used to measure student problems and developing programs that are in accordance with the assessments carried out.Keywords: Program Planning, Guidance and counseling, Standardized.